Pengaruh Akupresur Titik Perikardium 6 terhadap Mual Muntah pada Ibu Hamil Trimester 1 di PMB Ariyawati Susiandari, S.Tr.Keb., Bdn - Desfita Sari; Istiqomah Risa Wahyuningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background : Nausea and vomiting are common physiological complaints during the first trimester of pregnancy, caused mainly by increased levels of hCG, estrogen, and progesterone. Although considered normal, these symptoms can disrupt daily activities and decrease quality of life. If excessive, they may result in complications such as dehydration, electrolyte imbalance, weight loss, and hyperemesis gravidarum, which threaten maternal and fetal health. Management can involve pharmacological and non-pharmacological strategies. One safe, simple, and widely applied non-pharmacological approach is acupressure at the Pericardium 6 (PC6) point, believed to regulate the nausea center in the brain. Objective : This study aimed to determine the effectiveness of acupressure at the PC6 point in reducing nausea and vomiting among first-trimester pregnant women at PMB Ariyawati Susiandari, S.Tr.Keb., Central Lampung Regency. Method : This pre-experimental study used a one-group pretest–posttest design. Acupressure was performed at the PC6 point for 30 seconds, twice daily (morning and evening). Data were collected by observing changes in the intensity of nausea and vomiting before and after the intervention.The assessment was conducted by observing changes in the intensity of nausea and vomiting before and after the intervention. Result : Before acupressure, all respondents experienced moderate nausea and vomiting. After the intervention, most reported improvement, with symptoms reduced to the mild category. Statistical analysis with the Wilcoxon test showed a significance value of p=0.000, indicating a significant difference between pre- and post-intervention scores. Conclusion : Acupressure at the PC6 point effectively reduced nausea and vomiting in first-trimester pregnant women. This method can be recommended as a complementary non-pharmacological therapy that is safe, practical, and easily integrated into midwifery care.